PENGARUH PERPUTARAN KAS, MODAL KERJA, TOTAL ASET TERHADAP NET PROFIT MARGIN PADA PERUSAHAAN MAKANAN DAN MINUMAN DI BEI - Khodizah, Firda Nur; Sidik, Solihin (Jurnal Akuntansi, 2024)
This study aims to test the influence of cash turnover, working capital turnover, also total asset turnover on NPM. By using NPM as the dependent variable. The study method applied is descriptive and quantitative research. This study was processed using SPSS 16.0 as a hypothesis testing tool. The research period starts from 2020-2022, with research samples from 10 food and beverage sub-sector companies written on the IDX. With data analysis techniques consisting of the Classical Assumption Test and the Coefficient of Determination Test also the study model used is multiple linear regression. Research findings show that the working capital turnover variable has a significant impact on NPM. Meanwhile, the cash turnover also total asset turnover variables have no influence on NPM in food and beverage companies on the IDX.